1997
DOI: 10.1097/00007890-199701270-00010
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic and Patient Selection Strategies for Successful Utilization of Less Than 15 Kg Pediatric Donor Kidneys-Long Term Experiences With 40 Transplants1

Abstract: Renal transplantation using infant donors is associated with significantly less graft survival (GS) and increased morbidity, especially from very young and small donors. We report our results using specific strategies to determine which age and size donor require en bloc renal transplant reconstruction and associated immunologic protocols for optimization of subsequent GS. Forty cadaveric pediatric en bloc renal transplants were performed. Mean donor age was 23.6+/-18.4 months with subgroups: 2-12 months, n=14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 11 publications
2
43
0
1
Order By: Relevance
“…Because of the ongoing discrepancy between the organ supply and demand, kidneys are being transplanted from increasingly smaller pediatric donors (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Kidneys from small pediatric donors are often transplanted en bloc primarily to avoid small anastomotic vessel size and potentially limit thrombotic complications; however, some are transplanted as single kidneys to increase organ utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the ongoing discrepancy between the organ supply and demand, kidneys are being transplanted from increasingly smaller pediatric donors (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Kidneys from small pediatric donors are often transplanted en bloc primarily to avoid small anastomotic vessel size and potentially limit thrombotic complications; however, some are transplanted as single kidneys to increase organ utilization.…”
Section: Introductionmentioning
confidence: 99%
“…In their series of 40, Bretan et al 5 had one urinary leak (2.5%), and one dehiscence (2.5%). Both were repaired surgically.…”
Section: Discussionmentioning
confidence: 93%
“…In their series, Bretan et al 5 documented one graft loss (2.5%) of venous thrombosis due to hypercoagulable state. In their series of 22 en bloc kidney transplants, Satterthwaite et al 1 reported one venous thrombosis (4.5%) and two arterial thrombosis (9%), and all three grafts were lost.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Since the 1970s, pediatric donors ranging in age from 12 months to 5 years have provided both kidneys for transplantation into a single recipient. Advocates of this technically demanding approach have reported satisfactory outcomes despite the higher risks of surgical complications such as thrombosis and ureteral leak [4,22]. It has been said that pediatric grafts are resilient, with the potential for lifetime function.…”
Section: Conceptual Considerations In the Use Of Dual Renal Graftsmentioning
confidence: 99%